The Influence of Social Media on the Promotion of Sustainable Fisheries Management: A Case Study of Indonesian Crabs - Wahyu Prastiyawan; M.Imam Syairozi; M. Yaskun (SEAN Institute, 2024)
The swimming crab (Portunus pelagicus) is a leading Indonesian fishery commodity, largely exported to the United States. The Indonesian Swimming Crab Management Association (APRI) actively utilizes social media as a promotional tool for its sustainable fisheries program. This study aims to analyze the influence of APRI's social media on the interaction and effectiveness of Consumer Brand Engagement (CBE) in sustainable swimming crab fisheries programs in Indonesia. Data was collected over 14 days from 31 respondents who used social media platforms on Instagram, Facebook, LinkedIn, and YouTube using the Accidental Sampling method. Analysis was conducted using SmartPLS 3.2.9 to test the influence of four Brand Awareness factors (recall, recognition, alternatives, and keep recalling) on the interaction and effectiveness of CBE in four APRI programs (Swimming Crab Apartment, 5-Minute GTK, Swimming Crab Cultivation, and APRI Youth Innovation). The results indicate that the Swimming Crab Apartment and 5-Minute GTK programs are most familiar to respondents. Knowing and following APRI's social media significantly influences the interaction and effectiveness of CBE. Social media has proven effective as a digital marketing strategy for nonprofit organizations in promoting sustainable fisheries management programs and increasing public awareness.